2017
DOI: 10.1590/0102-311x00121016
|View full text |Cite
|
Sign up to set email alerts
|

A Convenção-Quadro para o Controle do Tabaco da Organização mundial da Saúde na agenda política brasileira, 2003-2005

Abstract: This study analyses the development of a tobacco-control agenda in Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
4
Order By: Relevance
“…In the multilateral sphere, Brazil had an intense performance at the WHO throughout its history, in which institutional action, protagonism in certain agendas, and the search for political prestige stand out (Ventura & Bueno, 2021, p. 436). For example, Brazil presided over the negotiations of the only covenant negotiated to date in the WHO concerning tobacco control, adopted in 2003 (Teixeira et al, 2017); in 2011, it hosted the WHO conference on the social determinants of health (WHO, 2011), having also integrated several times, and even chaired, the organization's executive board in recent years. Until 2019, in WHO forums Brazil has consistently advocated themes that are important to the national health agenda, as a diplomat who served in AISA publicly recognizes.
[…] despite the sequence of governments and Ministry of Health's managers, it is possible to verify a predominance of coherence and continuity, to the detriment of well‐defined ruptures, in the content of some macro‐themes related to Brazil's participation in the World Health Assembly over the last three decades, such as issues related to universal health coverage and access to medicines (Rezende, 2019, p. 43).
…”
Section: Coalescing the Principles Of Foreign Policy And The Unified ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the multilateral sphere, Brazil had an intense performance at the WHO throughout its history, in which institutional action, protagonism in certain agendas, and the search for political prestige stand out (Ventura & Bueno, 2021, p. 436). For example, Brazil presided over the negotiations of the only covenant negotiated to date in the WHO concerning tobacco control, adopted in 2003 (Teixeira et al, 2017); in 2011, it hosted the WHO conference on the social determinants of health (WHO, 2011), having also integrated several times, and even chaired, the organization's executive board in recent years. Until 2019, in WHO forums Brazil has consistently advocated themes that are important to the national health agenda, as a diplomat who served in AISA publicly recognizes.
[…] despite the sequence of governments and Ministry of Health's managers, it is possible to verify a predominance of coherence and continuity, to the detriment of well‐defined ruptures, in the content of some macro‐themes related to Brazil's participation in the World Health Assembly over the last three decades, such as issues related to universal health coverage and access to medicines (Rezende, 2019, p. 43).
…”
Section: Coalescing the Principles Of Foreign Policy And The Unified ...mentioning
confidence: 99%
“…In the multilateral sphere, Brazil had an intense performance at the WHO throughout its history, in which institutional action, protagonism in certain agendas, and the search for political prestige stand out (Ventura & Bueno, 2021, p. 436). For example, Brazil presided over the negotiations of the only covenant negotiated to date in the WHO concerning tobacco control, adopted in 2003 (Teixeira et al, 2017); in 2011, it hosted the WHO conference on the social determinants of health (WHO, 2011), having also integrated several times, and even chaired, the organization's executive board in recent years. Until 2019, in WHO forums Brazil has consistently advocated themes that are important to the national health agenda, as a diplomat who served in AISA publicly recognizes.…”
Section: Coalescing the Principles Of Foreign Policy And The Unified ...mentioning
confidence: 99%
“…These findings were expected and corroborate previous studies (Borzekowski & Cohen, 2013), however, unlike what was observed in the study by Fischer et al (1991), the recognition of cigarette brands was much lower than the recognition of logos and child characters in general. In 2011 Brazil adopted international recommendations for the regulation of tobacco products advertisement (Teixeira, Paiva, & Ferreira, 2017), so that, tobacco products advertising is limited to display of products at sales points (Portes, Machado, Turci, Figueiredo, Cavalcante, & Silva, 2018), it is possible to say that these governmental and societal actions have produced positive results, as shown in Table 3. p<0.01).…”
Section: Association Of Trademark Logosmentioning
confidence: 99%
“…No Brasil, observou-se um intenso e bemsucedido trabalho dos profissionais de saúde no sentido de construir políticas públicas e ações de controle ao tabagismo. A partir dos movimentos internacionais, esse fluxo ganhou como importante aliado o Ministério das Relações Exteriores, que potencializou e reforçou as negociações, alçando o Brasil uma posição de destaque no âmbito da CQCT-OMS (Teixeira, Paiva, Ferreira, 2017).…”
Section: Considerações Iniciaisunclassified
“…A partir dos movimentos internacionais, ações políticas potencializaram e reforçaram as negociações sobre a produção, comercialização e consumo do tabaco, o que deixou o Brasil em uma posição de destaque no âmbito da CQCT-OMS. Além disso, permitiram o alinhamento necessário ao recepcionamento do tratado na legislação nacional (Teixeira, Paiva, Ferreira, 2017).…”
Section: Políticas Públicas Para O Controle Do Tabagismounclassified